Challenges for sustainable nature-based tourism: Vilsandi National Park, Saaremaa Island, Estonia - Raadik-Cottrell, Jana, speaker; Cottrell, Stuart, speaker; Unidentified speaker (Colorado State University. Libraries, 2012)
The first protected area in the Baltic countries, Vilsandi National Park (VNP) is located near the west coast of Saaremaa Island, Estonia. As an archipelago, the area was designated a protected area at the beginning of the 20th century, became a national park in 1993, and designated as a wetland of international importance in 1997. VNP faces many challenges including a decentralized management structure, disjointed conservation plan, and lack of a visitor management plan. The purpose of the CCC fellowship is to enhance VNP and stakeholder capacity to manage nature conservation collaboratively, enhance sustainable livelihoods among tour operators via tourism to the park and to enhance the visitor experience. Data have been gathered via an onsite survey among international visitors, two initial workshops with VNP stakeholders and a second home owner survey conducted in summer/fall 2012. The project links conservationists, tourism specialists, NGOs, INGOs (PAN Parks, WWF), local municipal governments, and universities (Kuresaare College) in a collaborative process for conservation and tourism development. This presentation will highlight key findings of the various phases of the project thus far as well as challenges posed due to ongoing institutional changes protected area agencies face in Estonia.
Presented at the Spring 2012 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Collaborative Conservation in Practice: Innovations in Communities Around the World", February 7, 2012, Colorado State University, Fort Collins, Colorado. This series focused on the work that the CCC's Collaborative Conservation Fellows have been doing across the Western U.S. and around the world.
Dr. Stuart Cottrell is an associate professor in the Department of Human Dimensions of Natural Resources at Colorado State University whose research and teaching focus on sustainable tourism development and protected area management in EU protected areas. Stuart completed his PhD at Penn State University and taught at Wageningen University in the Netherlands for 6 years prior to coming to CSU in 2004.
Jana Raadik-Cottrell, PhD, Tourism lecturer/researcher at Kuresaare College of Tallinn University of Technology, is a nature-based tourism specialist/ lecturer with expertise on island community development via sustainable tourism on Saaremaa Island, Estonia. Jana completed her PhD in Human Dimensions of Natural Resources (HDNR) at Colorado State University and MS degree at Wageningen University in the Netherlands and is an adjunct faculty with HDNR.
Includes recorded speech and PowerPoint presentation.
Keywords: tourism development; Estonian Green Belt; coastal areas; sustainability